Are exchange rates more volatile with greater uncertainty? evidence from the PHP/USD exchange rate using GARCH-MIDAS models - Abreu, Marvin Kyle M.
This study explores the relationship between policy-related economic uncertainty and the volatility of the PHP/USD exchange rate returns. The study uses data constructed from Google Trends to measure uncertainty and employs GARCH-MIDAS models to differentiate the short-run and long-run components of exchange rate volatility. The results reveal that more policy-related economic uncertainty leads to decreased volatility in the long run, with uncertainty in the US having a greater effect than uncertainty in the Philippines. The counterintuitive outcomes may spring from the fact that uncertainty relates to the search for more information, which may exhibit a long-memory process where economic agents form beliefs that lead them to risk aversion. This study also separates market-related uncertainty from policy-related uncertainty using a regression method, where results show that market-related uncertainty does not significantly affect exchange rate volatility in the long run.